PEMANFAATAN WATER HAMMER UNTUK MENGHASILKAN SECONDARY FLOW DENGAN MENGGUNAKAN WATER PRESSURE TRANSFORMER - , RUSMANA; , Prof.Dr.Ing.Ir.Harwin Saptoadi, MSE ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This thesis discusses the use of pump engineering to get pressure wave of water hammer which generated two flows, that is low pressure primary flow and high pressure secondary flow. To make this happens, a water pressure transformer is constructed consisting of a water tank, a pump, 1 inch diameter galvanized pipes, pipe fittings, a pressure tank and valves.The measuring tools uses are pressure gauge, piezoelectric crystals and an oscilloscope. The water pressure transformer works as follows, first the pump turned on to flow water as high as 0.25 barg up to 1.65 barg, with 42.18 ltr/min debit, which is called primary flow. Then the solenoid valve is opened and closed repeatedly to make the flow immediately stop, and this makes pressure wave of water hammer, finally the pressure wave catches and strored in pressure tank, and flowed as secondary flow in which the pressure is higher then the pressure pump. The water pressure transformer produces maximum pressure from upto 28 times of that the primary pressure or approximately upto 28 times of working pressure pump. The pressure decreases when the primary pressure is increased and the other way around. The secondary flow debit becomes bigger when the pressure difference between primary and secondary flow is lower. The secondary flow debit becomes smaller when the pressure diference between the primary flow and secondary flow is higher